Dry Eye Disease and Pterygium - Rabeeya Munir, Munir Baig (Pakistan Journal of Ophthalmology, 2019)
Purpose: To find the changes in tear film and ocular surface in patients with pterygium. Study Design: A descriptive cross sectional study. Place and Duration of Study: Federal Government Services Hospital Islamabad during June 2013 to December 2014. Material and Methods: Dry eye questionnaire (DEQ-6) was administered by a trained researcher and DE tests were performed in all 256 willing subjects (136 with pterygium+120 control) age 30-76 years, by a single surgeon under same physical conditions after taking the consent and approval from Hospital Ethical committee. Diagnosis was made on presence of both symptoms and tear film parameters. Statistical analysis by simple percentages. Results: Dry eyes (DE) were found in 73 (53.7%) of the pterygium cases and 28 (23.5%) of the normal patients. In this study, 55 (40.5%) patients were symptomatic, defined as reporting 1 or more DE symptoms often or all the time. There were 53 (39%) patients that showed corneal fluorescein staining (CFS) and 69 (51%) showed plugging/mucous threads in both groups. Of 136 eyes with pterygium there were 91 (67%) males and 45 (33%) females. Out of these 50 (36.7%) patients showed normal tear film and 86 (63.2%) showed deranged functions. Moreover, among the 120 control eyes there were 73 (61%) males and 47 (39%)] females. Out of these 86 (72.3%) patients were normal and 34 (27.7%) had abnormal functions. These values were reduced indicating altered tear film in these patients. Conclusion: Pterygium disturbs tear functions causing dry eye like symptoms. Key Words: Dry eye, pterygium, tear film instability, ocular surface.